Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
two *(-x/(x - two) + one)/(x - two)^ two = zero
2 multiply by ( minus x divide by (x minus 2) plus 1) divide by (x minus 2) squared equally 0
two multiply by ( minus x divide by (x minus two) plus one) divide by (x minus two) to the power of two equally zero
2*(-x/(x - 2) + 1)/(x - 2)2 = 0
2*-x/x - 2 + 1/x - 22 = 0
2*(-x/(x - 2) + 1)/(x - 2)² = 0
2*(-x/(x - 2) + 1)/(x - 2) to the power of 2 = 0
2(-x/(x - 2) + 1)/(x - 2)^2 = 0
2(-x/(x - 2) + 1)/(x - 2)2 = 0
2-x/x - 2 + 1/x - 22 = 0
2-x/x - 2 + 1/x - 2^2 = 0
2*(-x divide by (x - 2) + 1) divide by (x - 2)^2 = 0
Similar expressions
2*(x/(x - 2) + 1)/(x - 2)^2 = 0
2*(-x/(x + 2) + 1)/(x - 2)^2 = 0
2*(-x/(x - 2) - 1)/(x - 2)^2 = 0
2*(-x/(x - 2) + 1)/(x + 2)^2 = 0
2*(-x/(x - 2) + 1)/(x - 2)^2 = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]